The Effectiveness Pertamina Pinky Movement Program: Implementation of The Concept of Creation Shared Value (CSV) - Rushartami, Meidina Arimbi; Winoto, Joyo; Suprehatin (School of Business, IPB University (SB-IPB), 2024)
Creating Shared Value (CSV) is the company's operational policy by increasing the company's competitive value and simultaneously advancing social and economic conditions for both the company and target recipients of the program. This program aims to shift the use of subsidized LPG to non-subsidized LPG and help MSEs develop their businesses. This study examines the effectiveness of the Pinky Movement Program regarding social and economic values for both companies and program participants. This study uses a survey method by collecting primary and secondary data. Primary data was obtained through questionnaires distributed to 392 program participants who were selected using purposive sampling. In total, 269 respondents completed the questionnaire. Secondary data was obtained from Pertamina, including sales, profits, brand reputation, the number of employees who contributed to the program and its implementation of the training program. Data analysis was performed using a paired sample t-test to compare the conditions before and when the The Pinky Movement Program was implemented. The study results show that the Pinky Movement program effectively created social and economic value from the perspective of program participants. However, from the Company's perspective, this program has not proven effective because there have been no positive changes in economic and social values before and during the program's implementation. The managerial implications that companies can carry out are continuing to run the Pinky Movement program as a social investment capable of providing positive results for the company, target recipients, and affected stakeholders, respectively. Keywords: creating shared value, economic value, micro small enterprises, non-subsidized LPG, social value